2020
DOI: 10.1021/acsearthspacechem.0c00134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dissolved Organic Matter on Porewater Hg and MeHg Concentrations in St. Louis River Estuary Sediments

Abstract: Inorganic mercury in sediments is a potential source of bioaccumulative methylmercury in the aquatic food web; however, in many cases, total mercury concentrations in the sediment alone cannot predict methylmercury production and distribution. Fish that primarily feed in the St. Louis River Estuary, a Great Lakes coastal wetland, have higher concentrations of methylmercury in their tissues than fish that primarily feed upriver or in Lake Superior; however, the exact sources of mercury to methylating microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(223 reference statements)
0
4
1
Order By: Relevance
“…Thus, we assumed that the reduced sulfur in porewaters might have contribute to the high accumulations of liquid-phase Hg in the FMB sediment. Meanwhile, the THg concentrations in the bulk sediment of the FMB were not statistically different from Kneer et al's [78] results, also reflecting the conditions that sediments with low THg concentrations facilitate the partitioning of Hg to porewaters. primary Hg species in the porewaters of the FMB were DOC-complexed compounds.…”
Section: Mercury Deposition In the Sedimentcontrasting
confidence: 62%
See 1 more Smart Citation
“…Thus, we assumed that the reduced sulfur in porewaters might have contribute to the high accumulations of liquid-phase Hg in the FMB sediment. Meanwhile, the THg concentrations in the bulk sediment of the FMB were not statistically different from Kneer et al's [78] results, also reflecting the conditions that sediments with low THg concentrations facilitate the partitioning of Hg to porewaters. primary Hg species in the porewaters of the FMB were DOC-complexed compounds.…”
Section: Mercury Deposition In the Sedimentcontrasting
confidence: 62%
“…We think the high THg levels in the porewaters might be related to reduced sulfur groups in the dissolved organic matter (DOM). Kneer et al [78] conducted a similar study in the St. Louis River estuary sediments, where they found that the high THg concentrations in porewaters were related to high levels of reduced sulfur groups in the DOM, and the conditions facilitating greater partitioning of the THg to the porewaters were linked to sediments with low THg concentrations. Although reduced sulfur groups were not measured in the FMB, relatively high sulfate concentrations were observed in the porewaters.…”
Section: Mercury Deposition In the Sedimentmentioning
confidence: 99%
“…Leaching is the initial phase of litter breakdown in aquatic environments and can rapidly release up to 30 % dissolved matter, primarily dissolved organic matter (DOM) within 24 h after immersion of litter (Gessner et al, 1999). It has been established that DOM is closely related to Hg mobility in terrestrial and aquatic ecosystems (Haitzer et al, 2002;Ravichandran, 2004;Kneer et al, 2020), given the strong affinity between Hg and reduced sulfur groups (i.e., thiols) in DOM (Xia et al, 1999). DOM with higher aromaticity has more thiol ligands and has a stronger correlation with Hg (Dittman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced sulfur is readily incorporated into dissolved organic matter (DOM) and makes up 0.5-3% of freshwater DOM by weight (Kneer et al, 2020;Manceau & Nagy, 2012;Poulin, Ryan, et al, 2017;Ravichandran, 2004). Sulfide produced during microbial sulfate reduction in aquatic environments is integrated into DOM by abiotic substitution and/or radical addition to functional groups containing unsaturated carbon-carbon bonds (Graham et al, 2017;Heitmann & Blodau, 2006;Hoffmann et al, 2012;Perlinger et al, 2002;Sleighter et al, 2014;Van Buren et al, 2021;Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chalcophilic trace and heavy metals (e.g., mercury, arsenic, lead, silver, gold, and copper) form DOM-metal complexes with reduced sulfur functional groups in DOM (Chuang et al, 2015;Stumm & Morgan, 1996). Most of these DOM-metal complexes are less toxic and/or bioavailable than their free metal counterparts, but toxicity varies among different forms of DOM and types of metals (Kneer et al, 2020;Schwartz et al, 2004). For example, Schwartz et al (2004) found that toxicity of copper, lead, and cadmium to rainbow trout in the presence of natural organic matter (NOM) varied greatly with NOM source, but the mechanisms for this variation are still poorly understood and require a finer study of NOM composition and sulfur content.…”
Section: Introductionmentioning
confidence: 99%